Relational Databases and Microsoft Access - McFadyen, Ron; Open Textbook Library (Open Textbook Library, 2016)
This text is a free introductory text that introduces MS Access and relational database design. The motivation is to support a second-year course on database systems which, to the student, is either a service course providing an introduction to database concepts, or, as a prerequisite for more advanced study in the field.
Table of ContentsPreface -- 1 Relational Databases and MS Access -- 2. Creating Tables -- 3. Creating Forms -- 4 Microsoft Access Queries -- 5 Relationships and the Relationships Tool -- 6 Microsoft Access Queries - Advanced -- 7 Entity Relationship Modelling -- 8 Mapping an ERD to a Relational Database -- 9 Data Definition Language (DDL) -- 10 Normalization -- Appendix A: Forms Involving Multiple TablesAppendix B: SuperTypes and Subtypes
In English.
Description based on online resource
Keywords: Computer Science -- Textbooks; Databases -- Textbooks